Development and evaluation of a multiplex polymerase chain reaction for the detection of salmonella species - Thong, Kwai Lin; Teh, C.S.J.; Chua, K.H. (Malaysian Society of Parasitology and Tropical Medicine, 2014)
The present study aims to develop a system which consists of four pairs of primers that specifically detects Salmonella spp., Salmonella serovar Typhi and Salmonella serovar Paratyphi A with an internal amplification control. The system, when applied in Polymerase Chain Reaction (PCR) under specific conditions, reaction mixture and cycling temperatures produced four bands; 784 bp, 496 bp, 332 bp and 187 bp. The DNA band 784 bp is present in all Salmonella spp., while the bands of 496 bp and 332 bp are only present in S. Paratyphi A and S. Typhi, respectively. An internal amplification control as indicated by the 187 bp shows the system is working in optimum condition in all the tests. This multiplex PCR was evaluated on 241 bacterial cultures and 691 naturally contaminated samples. Overall, this multiplex PCR detection system provides a single step for simultaneous detection of DNAs of Salmonella spp., S. Typhi and S. Paratyphi A.